The Use of Digital Comic in Developing Student's English Competence - Finaty Ahsanah; Dias Tiara Putri Utomo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This current study is aimed to know whether any improvement or not in using digital comics as the media on student’s English competence. The researchers used a quantitative approach with a pre-experimental design. This research was conducted at Universitas Muhammadiyah Lamongan and the sample was 42 pharmacist medical students. The instrument that was used to measure students’ English competence was the Test of English as a Foreign Language (TOEFL). The result of the test was analyzed by using statistical analysis of paired sample t-test. The finding showed that there was significant improvement before and after the treatment, it can be proved by the significant value of the pre and post-test which was 0.000 (2 tailed). Since the significance value (2-tailed) was less than 0.05, it means that the hypotheses of this study were accepted. In other words, the students positively received the use of digital comics for English learning activities. Therefore, digital comics can be assumed as an effective media or tool for enhancing students’ English competence.